2020
DOI: 10.1186/s12877-020-01601-z
|View full text |Cite
|
Sign up to set email alerts
|

Low serum albumin, aspartate aminotransferase, and body mass are risk factors for frailty in elderly people with diabetes–a cross-sectional study

Abstract: Background: Frailty is broadly characterized by vulnerability and decline in physical, mental and social activities and is more common in elderly patients with type 2 diabetes mellitus (T2DM). Frailty is closely associated with nutrition, muscle strength, inflammation, and hormones etc. In hormones, dehydroepiandrosterone sulfate (DHEA-S) and cortisol are suggested to be such candidates affecting frailty. Little investigation has been performed using a wider range of measures of frailty to clarify risk factors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Biomarkers related to inflammation and endothelial function, such as interleukin-6 (IL-6), soluble intercellular adhesion molecule-1 (s-ICAM-1), E-selectin, and soluble IL-6 receptor, were measured using ELISA (R&D Systems); fibrinogen was assessed by the coagulation method (Sysmex CA-1500; reagent: Dade Behring Company). In addition, serum albumin was measured, and a low serum albumin level (<4.0 g/dL) was defined according to previous research (31). As one of the B vitamins, folate was analyzed by chemiluminescence (Beckman CoulterACCESS R Immunoassay analyser).…”
Section: Biomarkersmentioning
confidence: 99%
“…Biomarkers related to inflammation and endothelial function, such as interleukin-6 (IL-6), soluble intercellular adhesion molecule-1 (s-ICAM-1), E-selectin, and soluble IL-6 receptor, were measured using ELISA (R&D Systems); fibrinogen was assessed by the coagulation method (Sysmex CA-1500; reagent: Dade Behring Company). In addition, serum albumin was measured, and a low serum albumin level (<4.0 g/dL) was defined according to previous research (31). As one of the B vitamins, folate was analyzed by chemiluminescence (Beckman CoulterACCESS R Immunoassay analyser).…”
Section: Biomarkersmentioning
confidence: 99%
“…Hypoalbuminemia was associated with frailty [ 6 ], cognitive impairment [ 7 ], and trace elements deficiency [ 8 ]. It was demonstrated that low serum albumin is a risk factor for frailty in elderly people with diabetes in a Japanese cross-sectional study [ 9 ]. In the longitudinal study, lower levels of serum albumin are associated with future decline in functional performance in older people [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies have found that serum albumin and body mass index (BMI), both are components of the GNRI, were independently correlated with frailty. 30 , 31 Furthermore, body weight is a common element between structures of the GNRI and the FRAIL scale. Taken together, use of the GNRI, a simple and readily available index, in routine clinical practice may be help clinicians quickly detect patients who are at risk of frailty, and allowing for early nutritional intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Yanagita et al 31 revealed that patients with lower serum albumin had a higher incidence of frailty, suggesting that low serum albumin could be a risk factor for frailty. However, albumin is variant by dehydration, trauma, and hepatic or renal impairment, which prevents it from being a sensitive and specific nutritional marker.…”
Section: Discussionmentioning
confidence: 99%